Intramuscular clozapine in the acute medical hospital: Experiences from a liaison psychiatry team - Gee, Siobhan (SAGE Open Med Case Rep, 2021)
We present two cases demonstrating safe and effective use of intramuscular clozapine for patients who are physically unwell in acute medical care settings. Both patients described were admitted to inpatient medical care units and required treatment with clozapine to control their psychotic symptoms, but were unable or unwilling to take oral clozapine. We describe the use of intramuscular clozapine in these patients, including dosing decisions, administration routes and frequency of dosing. Outcome was measured by a reduction in psychotic symptoms, sufficient to allow treatment for physical illness. Both patients successfully received intramuscular clozapine, allowing timely treatment of their physical health conditions. There were no adverse events, and significant improvement in their mental health presentations was achieved. We have shown that intramuscular clozapine is a safe and effective treatment for patients with serious mental health illness in the acute medical hospital.